Preferensi Makanan, Kebiasaan Makan, dan Status Gizi Anak Sekolah Full-day di Perkotaan: Food Preferences, Eating Habits, and Nutritional Status of Full-Day School Students in Urban Areas - Diana, Rian; Setyaningtyas, Stefania Widya; Arimbi, Agnessia Nanda (Universitas Airlangga, 2025)
Background: Food preferences play an important role in determining eating habits. School-age children spend a significant amount of time in school; therefore, school food environment can influence their eating habits and ultimately their nutritional status. Objectives: This study aimed to investigate eating habits and food preferences (with a focus on vegetables and snacks) among normal, overweight and obese of full-day school children in urban areas of Surabaya City. Methods: This cross-sectional study was conducted at a full-day elementary school in Surabaya City, Indonesia, involving 110 students. Dietary habits were assessed using a food frequency questionnaire, while nutritional status was evaluated by measuring weight and height. The students' nutritional status was determined using the BMI-for-age index with the WHO AnthroPlus software. Differences between variables were analyzed using the Chi-Square test, Fisher’s Exact test, and Likelihood Ratio test. Results: A high prevalence of overweight and obesity (41.8%) was observed in this study, with boys showing a higher prevalence than girls. Overweight/obese boys tended to eat more frequently and had a lower proportion of breakfast habits compared to girls, although these differences were not statistically significant (p-value>0.05). Food preferences for vegetables (carrot, spinach, water spinach) were similar between normal-weight and overweight/obese children. However, there were slight differences in snack preferences, with boys showing a greater preference for snacks than girls. Conclusions: The high prevalence of overnutrition among school-aged children, particularly boys, requires greater attention from parents and schools. Both home and school food environments should consistently promote healthy eating to improve children's nutritional status by encouraging regular breakfast habits in boys and providing healthier snack options.